PENGARUH BERBAGI PENGETAHUAN DAN BUDAYA TIM PADA KINERJA INOVASI LAYANAN (STUDI PADA HOTEL DI YOGYAKARTA) - , Nurul Hidayat, Dr. Nurul Indarti, Sivilokonom, Cand. Merc. ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Innovation is an essential requirement for hospitality sphere in order to enhance competitive advantage of the company. To enhance the capability of service innovation performance, company needs the knowledge which is gained from team culture knowledge sharing activities. This study focused on the hospitality industry because there was still being a lack of research about knowledge management in the hospitality industry than in other sectors. Knowledge sharing and team culture were proved had important influence on the service innovation performance. This study did not prove that team culture had a role as moderating variable of the influence of knowledge sharing on service innovation performance. Research framework that was developed in this study was tested with 230 employees working in the starred hotels in Yogyakarta. Data were collected using survey method with questionnaire as an instrument. Respondent responses in this study indicated that the influence of knowledge sharing and team culture on service innovation performance showed significant results. The main conclusion to be drawn from these findings are to achieve high service innovation performance, company should first develop knowledge sharing behavior and inculcate the better team culture on employees, which further could enhance competitive advantage and sustainability of the company.